2011
DOI: 10.1227/neu.0b013e318212badb
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Impact of Cognitive Deficits and Epilepsy on Quality of Life in Patients With Low-Grade Meningiomas

Abstract: The HRQOL of most patients with WHO Grade I meningiomas is comparable to that of the general population. However, HRQOL is worse in patients with major cognitive deficits and those using AEDs, irrespective of seizure control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 32 publications
6
94
0
6
Order By: Relevance
“…4 With regard to tumor laterality, patients with left-sided meningiomas had decreased verbal fluency and recall for verbal material compared with patients with right-sided meningiomas. This finding supports the well-established notion that the left hemisphere is dominant for language function 15 and is in agreement with previous studies reporting verbal deficits in patients with left-hemisphere benign, 28 low-grade, 9 and high-grade malignancy 12 tumors. Regarding the superoinferior axis, patients with skull base meningiomas had more deficits in memory components and long-term verbal and nonverbal memory than those with convexity meningiomas.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4 With regard to tumor laterality, patients with left-sided meningiomas had decreased verbal fluency and recall for verbal material compared with patients with right-sided meningiomas. This finding supports the well-established notion that the left hemisphere is dominant for language function 15 and is in agreement with previous studies reporting verbal deficits in patients with left-hemisphere benign, 28 low-grade, 9 and high-grade malignancy 12 tumors. Regarding the superoinferior axis, patients with skull base meningiomas had more deficits in memory components and long-term verbal and nonverbal memory than those with convexity meningiomas.…”
Section: Discussionsupporting
confidence: 93%
“…26 Patients with meningioma show significant long-term impairments in executive functioning; 6 those with skull base meningiomas perform lower on cognitive testing than those with convexity meningiomas, and those with leftsided meningiomas show more verbal memory deficits than those with right-sided meningiomas. 28 In general, neurocognitive deficits have been documented preoperatively in patients with meningiomas, suggesting that the tumor itself can cause neuropsychological disturbances. Furthermore, a number of studies have suggested that patients with surgically treated meningiomas present postoperatively with cognitive declines.…”
mentioning
confidence: 99%
“…1,36,8,9,11,12,1822,25,26,2830,3538,40,41,43,48,51–53,55,59,60, 6264,6870 All investigations were retrospective observational case series, and no prospective controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor removal has been reported to result in complete seizure freedom in 53-90 % of meningioma patients with preoperative seizures [6,16,15,25]. For the remaining patients who are not seizure free after surgery, quality of life is significantly decreased [47]. Interestingly, meningiomas and other slow-growing tumors are associated with epilepsy more often than rapidly growing tumors.…”
Section: Introductionmentioning
confidence: 99%